Shear stress modulation of IL-1β-induced E-selectin expression in human endothelial cells. - Ryan B Huang (Public Library of Science (PLoS), 2012)
Background Endothelial cells (ECs) are continuously exposed to hemodynamic forces imparted by blood flow. While it is known that endothelial behavior can be influenced by cytokine activation or fluid shear, the combined effects of these two independent agonists have yet to be fully elucidated. Methodology We investigated EC response to long-term inflammatory cues under physiologically relevant shear conditions via E-selectin expression where monolayers of human umbilical vein ECs were simultaneously exposed to laminar fluid shear and interleukin-1ß (shear-cytokine activation) in a parallel plate flow chamber. Results and conclusion Naïve ECs exposed to shear-cytokine activation display significantly higher E-selectin expression for up to 24 hr relative to ECs activated in static (static-cytokine). Peak E-selectin expression occurred after 8-12 hr of continuous shear-cytokine activation contrary to the commonly observed 4-6 hr peak expression in ECs exposed to static-cytokine activation. Cells with some history of high shear conditioning exhibited either high or muted E-selectin expression depending on the durations of the shear pre-conditioning and the ensuing shear-cytokine activation. Overall, the presented data suggest that a high laminar shear enhances acute EC response to interleukin-1ß in naïve or shear-conditioned ECs as may be found in the pathological setting of ischemia/reperfusion injury while conferring rapid E-selectin downregulation to protect against chronic inflammation.